Дорога Бузька до Кубраківки - Тищенко, К.М. (Сіверщина в історії України, 2022)
Місцевих назв-свідків контактів наддніпрянців із Сирією візантійської доби за століття виявлено чимало (пор. топоніми Трипілля, Халеп’я, Дамаски, Демешківці, Кир’яківка, Сорокотяги та ін.). Висновки топоніміки відповідають також і поширенню однокореневих прізвищ, і кільком українським словниковим запозиченням з сирійської. Тему тепер конкретизують свідчення участі наддніпрянців у духовному житті ранньої Візантії. Це епоха Соборів V–VІ ст., христологічних суперечок моно- і діафіситів, прозелітичної діяльності, уособленої в іменах тодішніх християнських ідеологів, підтримки походом Віталіана діафіситів Константинопольського патріархату. Ідентифіковано нові синхоричні основи КубрАк-/КубрЯк-, Анастас-/ Насташ-, Ладиг-, Северин-, Мелеш-: протоипи гр. κουμβάριον ‘вид корабля’, Ἀναστάσιος ‘Анастасій І’, сир. ܐܝܩܝܕܠܐ Lâdîqîyâ, Λαοδίκεια, ар. اللاذقية al-Lādhiq(iye) ‘Лаодікія Сирійська’, сир. ܣܿܘܪܘܸ ܣܸ Severus ‘Кир Север’ (Антіохійський), ܐܝܟܠܡ malkoyo Μελχίτοι ‘мел(е)кити’. Звідси відновлено цілий шар когерентних топоконтекстів того часу. During the last century, many local place names were identified as witnesses of the Middle Dnieper region contacts with Syria in Byzantine times (cf. the toponyms of Trypillia, Khalepya, Damasky, Demeshkivtsi, Kyryakivka, Sorokotiahy etc.). The conclusions obtained from the study of toponymy also correspond to the distribution of corresponding family names (Demeshko, Khalepchuk, Sorokotiaha), and specific Ukrainian lexical borrowings from Syriac (han’ba, hanyty, saraka, spyzharnia, norytsia, lylyknichka ‘shame, rebuke, poor man, hole, pantry, bat’), – all together testifies to the respectable depth of ethnic memory in the language we inherited. The topic is now continued by concrete evidence of the Dnieper people participation in the spiritual life of early Byzantium. This is the epoch of the Councils of the V–VI centuries, Christological disputes of monoand diaphysites and proselytizing activity embodied in the names of the then Christian ideologues, support of diaphysics of the Patriarchate of Constantinople by Vitalian’s campaign. A number of new synchoric bases have been identified within the recognized layer of events: KubrAk-/ KubriAk-, Anastas-/ Nastash-, Ladyh-, Sever(yn)-, Melekh- etc. – cf. their probable prototypes Gr. κουμβάριον ‘kind of the ship’, Ἀναστάσιος ‘Anastasius I’, Syr. ܐܝܩܝܕܠܐ lâdîqîyâ, Gr. Λαοδίκεια, Ar. اللاذقية al-Lādhiq(iye) ‘Laodicea in Syria’, Syr. ܣܘܿ ܪܘܸ ܣܸ Severus ‘Severus the Great’ (of Antiochia), ܐܝܟܠܡ malkoyo Μελχίτοι ‘melekites’. Based on them, a significant layer of coherent topocontexts of that period of history has been restored.